The concept of religion : defining and measuring contemporary beliefs and practices - Schilderman, Hans, 1959- (Koninklijke Brill, 2015)
In 'The concept of religion' Hans Schilderman edits a volume on the definition and empirical study of religion within the changing landscape of modern society. Now that we can no longer assume a simple harmony between the scientific concept of religion, church doctrine and practiced belief, issues concerning the definition and measurement of religion are becoming crucial issues to academic institutions. The contributing authors present empirical studies studying issues of lifespan and socialisation at school settings; of vocation and profession at church and hospital settings; and culture and nation of society at large. The volume offers a beautiful sample of the empirical study of religion; a conceptual and illustrative overview of the academic field for students and scholars in religion.